Sun‐induced fluorescence – a new probe of photosynthesis: First maps from the imaging spectrometer HyPlant - U. Rascher; L. Alonso; A. Burkart; C. Cilia; S. Cogliati; R. Colombo; A. Damm; M. Drusch; L. Guanter; J. Hanus; T. Hyvärinen; T. Julitta; et al. (Global Change Biology, 2015)
Variations in photosynthesis still cause substantial uncertainties in predicting photosynthetic CO 2 uptake rates and monitoring plant stress. Changes in actual photosynthesis that are not related to greenness of vegetation are difficult to measure by reflectance based optical remote sensing techniques. Several activities are underway to evaluate the sun‐induced fluorescence signal on the ground and on a coarse spatial scale using space‐borne imaging spectrometers. Intermediate‐scale observations using airborne‐based imaging spectroscopy, which are critical to bridge the existing gap between small‐scale field studies and global observations, are still insufficient. Here we present the first validated maps of sun‐induced fluorescence in that critical, intermediate spatial resolution, employing the novel airborne imaging spectrometer HyPlant . HyPlant has an unprecedented spectral resolution, which allows for the first time quantifying sun‐induced fluorescence fluxes in physical units according to the Fraunhofer Line Depth Principle that exploits solar and atmospheric absorption bands. Maps of sun‐induced fluorescence show a large spatial variability between different vegetation types, which complement classical remote sensing approaches. Different crop types largely differ in emitting fluorescence that additionally changes within the seasonal cycle and thus may be related to the seasonal activation and deactivation of the photosynthetic machinery. We argue that sun‐induced fluorescence emission is related to two processes: (i) the total absorbed radiation by photosynthetically active chlorophyll; and (ii) the functional status of actual photosynthesis and vegetation stress.

The Phenomenon of Ischemic Postconditioning of the Heart - L. N. Maslov; A. G. Mrochek; L. Hanus; J.-M. Pei; Y. Zhang; H. Wang; N. V. Naryzhnaya (Neuroscience and Behavioral Physiology, 2014)

Safety of atmospheric storage tanks during accidental explosions - E. Noret; G. Prod'homme; T. Yalamas; M. Reimeringer; J.-L. Hanus; D.-H. Duong (European Journal of Environmental and Civil Engineering, 2012)

Response of a tank under blast loading -- part I: experimental characterisation of blast loading arising from a gas explosion - D.H. Duong; J.L. Hanus; L. Bouazaoui; O. Pennetier; J. Moriceau; G. Prod’homme; M. Reimeringer (European Journal of Environmental and Civil Engineering, 2012)

Response of a tank under blast loading – part II: experimental structural response and simplified analytical approach - D.H. Duong; J.L. Hanus; L. Bouazaoui; X. Régal; G. Prod'homme; E. Noret; T. Yalamas; M. Reimeringer; P. Bailly; O. Pennetier (European Journal of Environmental and Civil Engineering, 2012)

Role of cannabinoid receptors in the regulation of cardiac contractility during ischemia/reperfusion - L. N. Maslov; O. V. Lasukova; A. V. Krylatov; L. O. Hanus; R. Pertwee; I. I. Ivanchuk; D. Crowford (Bulletin of Experimental Biology and Medicine, 2006)

Egg care by termite soldiers - R. Hanus; J. Šobotník; L. Cizek (Insectes Sociaux, 2005)

Reconstructing the Spatial Pattern of Trees from Routine Stand Examination Measurements - Mark L. Hanus; David W. Hann; David D. Marshall (Forest Science, 1998)
Reconstruction of the spatial pattern of trees is important for the accurate visual display of unmapped stands. The proposed process for generating the spatial pattern is a nonsimple sequential inhibition process, with the inhibition zone proportionate to the scaled maximum crown width of an open-grown tree of the same species and same diameter at breast height as the subject tree. The results of this coordinate generation procedure are compared with mapped stem data from nine natural stands of Douglas-fir at two ages by the use of a transformed Ripley's K(d) function. The results of this comparison indicate that the proposed method, based on complete tree lists, successfully replicated the spatial patterns of the trees in all nine stands at both ages and over the range of distances examined. On the basis of these findings and the procedure's ability to model effects through time, the nonsimple sequential inhibition process has been chosen to generate tree coordinates in the VIZ4ST computer program for displaying forest stand structure in naturally regenerated young Douglas-fir stands. For. Sci. 44(1):125-133.